1993
DOI: 10.3354/meps095125
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the Dioaccumulation and turnover of polonium-210 and lead-210 in marine shrimp

Abstract: The experimental accumulation of 210Po and 'lOPb from seawater alone and from seawater and food was studied in the laboratory with the benthic shrimp Lysrnata seticaudata. Shrimp accumulated both radionuclides from water for 21 d, reaching whole body concentration factors [CF = (Bq g-' of shrimp wet wt)/(Bq ml-' filtered water)] of 139 k 28 for "OPo and 682 + 149 for 'l0Pb. When uptake was from water only, tissue analyses revealed that radionuclide accumulation was mainly due to external adsorption. Accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Ionic species are probably adsorbed onto shrimp exoskeletons through chelation by functional groups on organic surfaces as seen with other divalent metals (Carvalho and Fowler 1993). One of our shrimp in the free-ion treatment molted shortly before the animal was to be sacrificed for sampling, and although this animal was not included in our analysis, it provided some data on the activities of the intact exoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ionic species are probably adsorbed onto shrimp exoskeletons through chelation by functional groups on organic surfaces as seen with other divalent metals (Carvalho and Fowler 1993). One of our shrimp in the free-ion treatment molted shortly before the animal was to be sacrificed for sampling, and although this animal was not included in our analysis, it provided some data on the activities of the intact exoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that it contained a substantial proportion (Ba 9%, Sn 14%, Cd 16%, Hg 18%, Ag 21%, Fe 48%, Mn 56%, Zn 70%, and Co 72%) of the total animal activity, although we do not know how much of this activity was due to surficial adsorption. Carvalho and Fowler (1993) found that after 21 d of uptake via solution, the exoskeleton of the caridean shrimp Lysmata seticaudata accounted for 27.5 and 36% of total activity of 210 Po and 210 Pb, respectively. Only three of our animals molted, and there was no evidence that any of the animals we sampled and used for final analysis had molted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aquatic organisms can acquire trace elements from food, suspended particles or directly from the water (Carvalho and Fowler, 1993). Many of these pollutants are nonbiodegradable compounds and dangerous due to their innate ability to constantly remain within the ecosystem (Hernandez-Hernandez et al, 1990).…”
mentioning
confidence: 99%